Escapism - Sopčić, Barbara (Studia Historica Slovenica, 2020)
Until recently, escapism was generally seen as a negative phenomenon, due to its common conceptualization as an escape from reality; however, with the new model a more positive approach, distinguishing between self-suppression and self-expansion, began. In our study, we looked into the mechanisms underlying both components of escapism, where a sample of 147 students individually chose their escapist activity. Building on the two-dimensional conceptualization of escapism, we assumed that self-suppression would be associated with higher levels of self-alienation, while escapism as self-expansion would be related to higher levels of dispositional mindfulness and indirectly to a tendency to achieve flow. Results confirmed that self-suppression escapism and self-alienation share a positive correlation, with later also being a significant predictor of self-suppression escapism. However, contrary to our prediction, self-expansion escapism is not associated with dispositional mindfulness, nor does it represent a significant moderator in the relationship between self-expansion and flow. This study has extended the current understanding of escapist activities' complex nature in relation to psychological factors. Moreover, we contributed to the currently still sparse knowledge of escapism, and shed light on its positive side, which certainly exists, since escapism can lead not only to suppression of self but also to its enrichment and expansion.
Keywords: alienation; čuječnost; čutno zaznavanje; escapism; eskapizem; mindfulness; odtujenost; psihologija; self; self-expansion; self-suppression